Methods of assessment of the impact of COVID-19 on community dietary patterns - Kwofie, Mabel Kyei; Kwofie, Ebenezer Miezah; Ngadi, Michael (AKADEMIYA2063, 2021)
Food provides the nutrients and energy that are essential for human health. Poor diet is associated with major chronic diseases such as obesity, diabetes, cancer, and respiratory and cardiovascular diseases that persist in both developing and developed nations (Popkin, Adair, and Ng 2012). These diseases contribute to high mortality rates worldwide. A public health challenge is how to reduce exposure to chronic diseases through reinforcement of healthy lifestyles and dietary patterns within populations (Gil et al. 2014). Associations between diet and health outcomes have been observed through longitudinal or retrospective case-control studies, and cross-sectional research studies. Dietary patterns involving healthy food consumption habits among individuals are beneficial in the prevention of diet-related health risks. In dietary patterns studies, it was observed that intake of distinct food combinations is more essential than single nutritive substance or foodstuff consumption (Newby and Tucker 2004). Diet quality assessments that consider overall diet and categorize populations by healthy consumption behavior are crucial tools in monitoring changes within a given population. Broadly, there are two methods—namely, a priori and a posteriori—that have been employed in assessing dietary patterns. The a priori approach assesses consumers’ adherence to and application of specific dietary recommendations, whereas the a posteriori approach is data-driven and uses multivariate statistical approaches.